High expression of SIGLEC7 may promote M2-type macrophage polarization leading to adverse prognosis in glioma patients - An, Wenhao; Ren, Changyuan; Yuan, Lei; Qiu, Zhiqiang; Wang, Peishen; Cheng, Yanwen; He, Zi; Han, Xinye; Li, Shouwei; An, Yihua (Frontiers in Immunology, 2024)
SIGLEC7, known as sialic acid-binding immunoglobulin-like lectin 7, is present in various immune cells, notably macrophages, where it exerts significant influence over immune homeostasis and the response to cancerous cells. However, research into the mechanism of action of SIGLEC7 in glioma patients is currently relatively limited. In this study, we conducted a thorough analysis of glioma patient data from both the TCGA and a cohort comprising 693 samples from the CGGA database. Our findings revealed a noteworthy increase in SIGLEC7 expression within high-grade gliomas, especially within the more aggressive mesenchymal subtype. Survival analysis demonstrates a significant decrease in survival rate among glioma patients expressing high levels of SIGLEC7. Analysis of gene ontology and KEGG indicates that SIGLEC7 primarily participates in immune and inflammatory responses, with a close association to pathways expressed in tumors. The GSVA results revealed a strong negative correlation between SIGLEC7 and tumor immune regulation. Further research indicates that the expression of most immune checkpoints is positively correlated with SIGLEC7, suggesting that SIGLEC7 may synergistically contribute to the immunosuppressive properties of gliomas alongside other immune checkpoints. In addition, immune function analysis showed that SIGLEC7 can inhibit the secretion of B cell IgG, while immune cell infiltration analysis clearly demonstrated the promoting role of SIGLEC7 in glioma development, with its expression significantly positively correlated with the infiltration level of M2-type macrophages. Combining single-cell sequencing technology with tissue and cell experiments, we hypothesize that SIGLEC7 enhances the polarization of macrophages towards the M2 phenotype, thereby promoting glioma invasiveness through the immunosuppressive effects of M2-type macrophages. Finally, the establishment of Cox regression analysis and survival prediction models indicates that high expression of SIGLEC7 is a significant adverse prognostic factor for glioma patients. These findings provide important clues for further investigating the potential role of SIGLEC7 in the treatment of gliomas.